Hydrogeochemical characterization and quality evaluation of groundwater suitability for domestic and agricultural uses in the state of Qatar - Ayesha Y. Ahmad (14152779) (2020)
This study aims to investigate the groundwater (GW) quality in Qatar to be utilized in domestic and agricultural uses. The integrated physiochemical analysis along with hydrochemical faces analysis, geochemical modeling, statistical and geostatistical analysis was conducted. The results showed that the GW samples mainly have the following cations Na+ > Ca2+ > Mg2+ >K+ abundantly, while Cl− > SO42− > HCO3− > NO3− were the main anions. The obtained analytical values of the GW samples were plotted on Piper, Schoeller, Ternary, Ludwig Langelier, Giggenbach Triangle, Durov, and stiff graphs. The hydrogeochemical facies and the obtained graphs confirmed that most of the analyzed GW samples fall into two types of water namely calcium-chloride-type (SO4–Cl and Ca–Mg) and sodium-chloride-type (SO4–Cl and Na–K). Three principal components were yielded from the principal component analysis (PCA), which are the first principal component (PC1), second principal component (PC2), and third principal component (PC3) with ≥1 Eigenvalues, and total variance of 49, 31, and 19.9%, respectively. A positive loading of Mg, Th, Sr, Ca, TDS, SO4, Li, Cl, F, Br, Cd, K, Ba, and Na has been shown by the PC1; representing the factors which are contributing to the high salinity of the GW due to the salt water intrusion and the mineralization of rocks and soil which is supported by the water type classification and saturation indices. The PC2 showed a negative loading of U, Al, Se, Mo, Mg, and temperature, which could be associated with a localized sedimentary depositional or hydrogeochemical environment. The PC3 showed a positive loading of Ni, Zn, Be, pH, Cu, Co, Fe, B, V, and TOC, which indicates the dissolution and precipitation (reducing and oxidizing factor) such as iron which is a redox-sensitive variable. Other Information Published in: Groundwater for Sustainable Development License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.gsd.2020.100467